DO WE NEED THE GENUS LEVEL IN THE RUSSIAN SOIL CLASSIFICATION SYSTEM? - M. I. Gerasimova (Бюллетень Почвенного института им. В.В. Докучаева)
The level of genus in the “Classification and diagnostics of soils of the USSR”, 1977 is discussed as applied for diverse purposes. It was very often required in soil surveys to indicate details of soil processes, current or inherited features when compiling small- and medium-scale soil maps. In the recent classification of Russian soils, genus level is mostly used for the analytical characteristics of soils, whereas its former functions were transferred to the subtype level; for example, red color of parent material corresponds to “red-profile” subtype. In the updated classification system of soils of Russia, it is proposed to expand the sphere of the genus level application over a broader set of phenomena, to update the criteria for different genera, and to arrange genera in groups like those for genetic properties, which serve as criteria to identify subtypes. The following preliminary groups of genera may be specified: analytical including genera related to chemical soil pollution, lithological (particular parent materials), temporal for ephemeral features, pedogenetic – disclosing or indicating mechanisms of soil processes.